Assessment of Accessibility of Information and Communication Technology by Gender among Famers in Taraba State, Nigeria - D. Bakari; S. A. Gisilanbe; P. Samuel (Archives of Current Research International, 2018)
Information and Communication Technology (ICT) is the future of communication and it is integral to human interaction and ease of doing things. It is important in the 21st century for almost all human endeavors. This study was aimed to assess the accessibility of ICT by Gender among Famers in Taraba State, Nigeria. Both purposive and multi-stage random sampling techniques were adopted for the selection of 214 respondents. Primary data were collected using structured questionnaires and interview techniques administered on respondents and analyzed using descriptive statistics and independent t-test statistical tool. Results indicated that mobile phone (M=3.71 for males and M=3.60 for females) radio (M=3.68 for males and M=2.69 for females) and television (M=3.04 for males and M=2.59 for females) were the best means of accessing ICTs by gender. However, males had more access to radio, television and mobile phone than females. In access to ICTs by location, results revealed that mobile phone (M=3.67 for urban and M=3.62 for rural), radio (M=3.17 for urban and M=3.2 for rural), television (M=3.16 for urban) and internet (M=2.67 for urban) were most readily accessible among both urban and rural farmers whereas television and internet were best accessible in the urban area. Results further showed that there was a statistically significant difference at p<0.01 for access to radio between male and female respondents (t=8.718), television between male and female respondents (t=3.552), internet between male and female respondents (t=4.182) and computer between male and female respondents (t=3.858). This indicated that male had more access to ICTs than females in the study area. Women are actively involved in improving soil texture and structure and also, improving soil fertility and productivity in the study area. Hence, empowering rural farmers by providing them with adequate infrastructural facilities and basic amenities that can enhance their access to ICTs is imperative. This will go a long way to alter inequality of access between rural and urban communities and also increase their access to soil inputs like fertilizers and other soil tillage tools for crop production in the study area.